The Role of Sports Teachers in the Development of Adaptive Physical Education in Special Schools - Benny Aprial M; Lela Santika (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2023)
The aim of this research is to obtain data and information about the role of sports teachers in the development of adaptive physical education at SLB TPAC and SLB Pembina in learning activities. The background is the findings in the field, that there is a need for sports teachers in adaptive physical education learning in Special Schools in adaptive physical learning. This research uses a quantitative approach with descriptive research type. The method used in this research is a survey method using interview and questionnaire techniques. The number of respondents in this study was 19 people, obtained from calculating the TPAC SLB and Pembina SLB samples. The results of this research show that in learning planning 61.65% of teachers are capable of making plans, in implementing learning 66.84% of teachers are capable, and in learning assessment 66% of teachers are capable and play a role in adaptive physical learning.